Fe3C‐Co Nanoparticles Encapsulated in a Hierarchical Structure of N‐Doped Carbon as a Multifunctional Electrocatalyst for ORR, OER, and HER - Yang, Chun Cheng; Zai, Shi Feng; Zhou, Yi Tong; Du, Li; Jiang, Qing (Advanced functional materials, 2019)
Rational design of non‐noble metal catalysts with robust and durable electrocatalytic activity for oxygen reduction reaction (ORR), oxygen evolution reaction (OER), and hydrogen evolution reaction (HER) is extremely important for renewable energy conversion and storage, regenerative fuel cells, rechargeable metal–air batteries, water splitting etc. In this work, a unique hybrid material consisting of Fe3C and Co nanoparticles encapsulated in a nanoporous hierarchical structure of N‐doped carbon (Fe3C‐Co/NC) is fabricated for the first time via a facile template‐removal method. Such an ingenious structure shows great features: the marriage of 1D carbon nanotubes and 2D carbon nanosheets, abundant active sites resulting from various active species of Fe3C, Co, and NC, mesoporous carbon structure, and intimate integration among Fe3C, Co, and NC. As a multifunctional electrocatalyst, the Fe3C‐Co/NC hybrid exhibits excellent performance for ORR, OER, and HER, outperforming most of reported triple functional electrocatalysts. This study provides a new perspective to construct multifunctional catalysts with well‐designed structure and superior performance for clean energy conversion technologies. A hybrid material of Fe3C‐Co/NC is synthesized through a facile template‐removal method, where Fe3C and Co nanoparticles are encapsulated in a nanoporous N‐doped hierarchical structure integrating 1D carbon nanotubes and 2D carbon nanosheets. As a multifunctional electrocatalyst, such a hybrid exhibits superior catalytic performances for oxygen reduction reaction, oxygen evolution reaction and hydrogen evolution reaction simultaneously.